Representações sociais da identidade de docente readaptado no magistério público do Distrito Federal - Neris, Marco Antonio da Luz (2018)
Introduction. The justification for this study is due to the significant increase of chronic illness of teachers in conducting class and associated with this, the numerical growth of teachers readjusted in the school context. Goals. To investigate social representations in interaction with social identity of teachers readjusted by teacher’s regents, managers and teachers refitted in the school context of the secretariat of State of Education of the Federal District – SEDF. Method. A research of qualiquantitativa character was carried out, with the purpose of examining the social representations of faculty readjusted by the teachers Regents, school managers and teachers readjusted in the school context and to verify the changes in Professional identity of readjusted faculty. The number of participants in the survey corresponded to (n = 400) sampled subjects of convenience, subdivided into 03 (three) groups, i.e. (n = 240) Faculty Regents of Children's school, fundamental, medium and technical, (n = 80) School Managers of Schools of education, elementary, medium and technical and (n = 80) Teachers readapted in acting in the schools of elementary, elementary, middle and technical education of all regional teaching of the Secretariat of State of Education of the Federal district. The technique of the free evocations of the Central core theory of Fabric (1994), was chosen as an instrument for obtaining the content and access to the internal structure of the social representations of the teachers Regents, school managers and teachers refitted in Relation to the social representations of faculty refitted in the school context. The materials that were used for the construction of the research data are: consent term free and clarified-fics; Printed form, structured, with identification of the participants of the survey, containing the spaces for the words or expressions for the numbering corresponding to the order of the Evocations performed. Analysis of the data. For the analysis and interpretations of the information data of the evocations obtained, as well as, to enable the process of production of knowledge, was used in this research the software EVOC-Ensemble of programmes permettant l Analisyse des evocations. Final considerations. the results demonstrate and confirm the hypothesis that the "professional identity of readjusted faculty" is situated in the "identity of the situation", portrayed by Dubar (2006), as being a form of professional identity shared By a group in need of "collective memory" and stigmatized by the sharing of a devalued condition, that is, it arises from the rupture of professional identity of teacher in conducting class, coming from the set of malaises, the process of Precarious of the teaching work and the teaching illness, culminating with the functional readjustment and the change of place of performance in the school context.